Measurement of multidifferential cross sections for dijet production in proton–proton collisions at $$\sqrt{s} = 13\,\text {Te}\hspace{-.08em}\text {V} $$ s = 13 Te V - CMS Collaboration (European Physical Journal C: Particles and Fields)
Abstract A measurement of the dijet production cross section is reported based on proton–proton collision data collected in 2016 at $$\sqrt{s}=13\,\text {Te}\hspace{-.08em}\text {V} $$ s = 13 Te V by the CMS experiment at the CERN LHC, corresponding to an integrated luminosity of up to 36.3 $$\,\text {fb}^{-1}$$ fb - 1 . Jets are reconstructed with the anti- $$k_{T} $$ k T algorithm for distance parameters of $$R=0.4$$ R = 0.4 and 0.8. Cross sections are measured double-differentially (2D) as a function of the largest absolute rapidity $$|y |_{\text {max}} $$ | y | max of the two jets with the highest transverse momenta $$p_{T}$$ p T and their invariant mass $$m_{1,2} $$ m 1 , 2 , and triple-differentially (3D) as a function of the rapidity separation $$y^{*} $$ y ∗ , the total boost $$y_{\text {b}} $$ y b , and either $$m_{1,2} $$ m 1 , 2 or the average $$p_{T}$$ p T of the two jets. The cross sections are unfolded to correct for detector effects and are compared with fixed-order calculations derived at next-to-next-to-leading order in perturbative quantum chromodynamics. The impact of the measurements on the parton distribution functions and the strong coupling constant at the mass of the $${\text {Z}} $$ Z boson is investigated, yielding a value of $$α _S (m_{{\text {Z}}}) =0.1179± 0.0019$$ α S ( m Z ) = 0.1179 ± 0.0019 .